Orthotics & prosthetics in rehabilitation - Lusardi, Michelle M.; Jorge, Milagros; Nielsen, Caroline C. (Elsevier Saunders, 2013)
The most comprehensive physical therapy text available on the topic, Orthotics & Prosthetics in Rehabilitation, 3rd Edition, is your one-stop resource for clinically relevant rehabilitation information. Evidence-based coverage offers essential guidelines on orthotic/prosthetic prescription, pre- and post-intervention gait assessment and outcome measurement, and working with special populations.